Human Presence and Robotic Mediations: An Alternative Framework for Explicating Human Enhancement - Pericle Salvini (Humana.Mente: Journal of Philosophical Studies, 2014)
In this essay I propose an alternative theoretical framework for explicating human enhancement. The framework is based on the concepts of reciprocity, which I consider a fundamental aspect of human presence, and of mediation, which I consider a fundamental aspect of the relation between human beings and science and technology. I argue that enhancement is given by the way in which technological and scientific mediation alters the structure of the network of reciprocity characterising human presence. As a matter of fact, technological mediation may turn the reciprocity of presence into a unilateral relation, which prevents any form of response. The lack of responsibility, here understood as the possibility to respond back, is determinant for the generation of a situation of power and for eliciting moral disengagement. The framework will be applied and discussed with reference to robotics technologies.